Technical course of nursing: reasons of entrance in the perception of your students - Alencar, Girlene Maria Magalhães Cavalcante de; Vasconcelos, Francisca de Fátima; Brito, Daniele Mary Silva de; Moreira, Thereza Maria Magalhães (Rev Rene, 2002)
This study aims to investigate the students’ reason entrance in a nursing technical course. The qualitative descriptive study was developed in February of 2002, with 56 students of private nursing technical course. Ethical aspects were considered. Data were organized in thematic categories and analyzed, showing the reasons: social concern, previous contact with profession, it likes to care, interest to care, interest by the area or by kindred areas, presents areas, presents of work and own vocation/need or vocation/need of somebody else. The discoveries are important for orientation of nursing technical courses. It’s recommended to accomplish new researches in other institutions, and in public courses too.